The Penguin companion to classical music - Griffiths, Paul 1947- (Penguin Books, 2004)
This work explores the lives and achievements of figures in the field of music, discusses individual works, offers plot synopses of operas and ballets, and considers the careers of major performers. It looks at historical movements and trends, the evolution of musical instruments and the development of different forms of music, explains the vocabulary of classical music and the technical teral terms that describe how works are written and performed.
Keywords: Musik; Music -- Bio-bibliography; Music -- Dictionaries; Klassische Musik; Führer; Wörterbuch